Pre-treatment effects on hydration behaviour of cement bonded boards made from eremospatha macrocarpa and laccosperma secundiflorum canes (2012)
"The effects of pre-treatments on the setting time (tmax) maximum hydration temperature (Tmax) and time ratio (tr) of two rattan species (Eremospatha macrocarpa and Laccosperma secundiflorum) particles mixed with portland cement were investigated. The untreated E. macrocarpa and L. secundiflorum had tmax, Tmax and tR of 12.4 and 11.9h, 59.1 and 58.3oC, 1.1 and 1.1, respectively while cold water treated E.macrocarpa and L.secundiflorum had tmax, Tmax and tR of 10.7 and 10.0h, 63.3 and 65.1oC, 1.0 and 0.9, respectively. CaCl2 pre-treatment E. macrocarpa and L. secundiflorum had tmax , Tmax and tR were 5.2 and 5.6h, 83.7 and 78.6 oC,0.5 and 0.5, respectively. Therefore, CaCl2 pre-treatment significantly served as an accelerator to improve cement hydration parameters better than cold water. Findings showed that L. secundiflorum inhibited cement setting more than E.macrocarpa due to its higher sugar content. "